Potensi Probiotik Bakteri Asam Laktat Asal Madu dari Tiga Jenis Lebah yang Berbeda - Iffa Illiyya Fatma; Lilis Nuraida; Didah Nur Faridah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Certain strains of Lactic acid bacteria (LAB) especially from the genus of Lactobacillus and Bifidobacteria have been recognized to have health beneficial effect as probiotics. Honey has been known to have health beneficial effects and contains lactic acid bacteria. However, information pertaining the characteristics of LAB from honey is still limited. The present research aimed to isolate LAB from different types of honey and to evaluate their potency as probiotic. The LAB were enumerated and isolated from honey produced by three different honeybees: Apis cerana, Heterotrigona itama, and Trigona laeviceps. The results showed the count of LAB in three different honey ranged from 5.0x101 to 2.3x107 CFU/mL and affected by different time of sampling. The highest of average LAB count was found in honey of Heterotrigona itama. There were 48 Gram positive catalase-negative bacterial isolates obtained from the three different honey types. Twelve isolates were selected based on their survival in bile salt. The twelve selected isolates were capable of growing in MRSB pH 2.5, and MRSB containing 0.3% bile salt. They also exhibited strong antibacterial activity against pathogenic bacteria. Identification based on 16S rRNA revealed that of the twelve isolates, nine were identified as Lactiplantibacillus plantarum and three others as Pediococcus acidilactici. The twelve isolates showed high survival at low pH dan bile salt and exhibited antimicrobial activity against pathogen, hence they are considered as probiotic candidates.